2022
DOI: 10.1038/s41467-022-28061-w
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of the exocytosis protein STX4 in skeletal muscle remediates peripheral insulin resistance and alters mitochondrial dynamics via Drp1

Abstract: Mitochondrial dysfunction is implicated in skeletal muscle insulin resistance. Syntaxin 4 (STX4) levels are reduced in human diabetic skeletal muscle, and global transgenic enrichment of STX4 expression improves insulin sensitivity in mice. Here, we show that transgenic skeletal muscle-specific STX4 enrichment (skmSTX4tg) in mice reverses established insulin resistance and improves mitochondrial function in the context of diabetogenic stress. Specifically, skmSTX4tg reversed insulin resistance caused by high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…As one of the important mechanisms for inducing insulin resistance, skeletal muscle mitochondria play a key role in regulating insulin resistance [ 34 ]. Merz et al demonstrated that skeletal muscle-specific STX4 remediates HFD-induced insulin resistance via suppressing mitochondrial fission [ 35 ]. The reduced mitochondrial capacity in skeletal muscle is suggested to underlie IR development in obesity and type 2 diabetes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the important mechanisms for inducing insulin resistance, skeletal muscle mitochondria play a key role in regulating insulin resistance [ 34 ]. Merz et al demonstrated that skeletal muscle-specific STX4 remediates HFD-induced insulin resistance via suppressing mitochondrial fission [ 35 ]. The reduced mitochondrial capacity in skeletal muscle is suggested to underlie IR development in obesity and type 2 diabetes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transfected myoblasts expressed ~2-fold more PAK1 protein compared to endogenous PAK1 in the control pCMV-vector-transfected myoblasts (Figure 5B), and incubation of INS-1 832/13 b-cells with CM from the PAK1overexpressing myoblasts resulted in enhanced GSIS relative to that of the b-cells incubated with CM from vector-expressing myoblasts (Figure 5C, bar 4 vs. bar 2); b-cell insulin content was unchanged (Figure 5D). The observation that CM from muscle cells overexpressing PAK1 enhances GSIS is unique to PAK1 overexpression to date, as other factors like Syntaxin 4 overexpressed (STX4 OE) in L6 myoblast cells had no enhancing effect upon GSIS compared with vector-transfected control cells (STX4 OE=11 ng insulin/mg total protein at 1 mM glucose; 24 ng insulin/mg total protein at 20 mM glucose, n=4, p > 0.05 vs. vector control (41). These data suggest that PAK1 levels in the skeletal muscle may mediate the release of factors into the circulation that crosstalk with the pancreatic b-cells.…”
Section: Pak1 In Skeletal Muscle Mediates Crosstalk Between Skeletal ...mentioning
confidence: 97%
“…In the skeletal muscle of diabetic mice, STX4 mRNA levels are significantly reduced ( 93 ), suggesting that STX4 deficiency may be important for diabetes development, and that re-expression of STX4 may be a therapeutic strategy to restore insulin sensitivity and reverse T2D. In alignment with this point of view, a recent study showed that enrichment of STX4 (~2 fold) in skeletal muscle remediates peripheral insulin resistance in obese mice, even under conditions of persisting intake of high-fat diet ( 94 ). Collectively, these findings highlight the important role and therapeutic potential of STX4 in remediating insulin resistance in skeletal muscle.…”
Section: The Physiologic and Mechanistic Roles Of Snares In Glut4 Ves...mentioning
confidence: 99%
“…High-fat diets are known to increase mitochondrial fission and mitophagy ( 184 ), a hallmark of high-fat diet-induced diabetes. STX4 enrichment reversed both skeletal muscle insulin resistance and mitochondrial fragmentation and dysfunction in high-fat diet-fed mice ( 94 ). The mechanism is currently believed to involve suppression of mitochondrial fission.…”
Section: Atypical Roles Of Snare Proteinsmentioning
confidence: 99%
See 1 more Smart Citation